Characterisation of quorum quenching actinobacteria isolated from mangrove swamps exhibiting lactonase activity / Norshazliza Ab Ghani - Norshazliza , Ab Ghani (2017)
Sophisticated communication systems that link cell density and gene expression in many bacteria species aims to regulate a broad range of biological functions. Such cell-to-cell communication, termed quorum sensing (QS), depends on the production, diffusion, and recognition of small signal molecules. Quorum quenching (QQ), is a process that interrupt the key process of QS and could be potentially used to prevent microbial infections. Actinobacteria produce numerous secondary metabolites with diverse pharmacological activities. This study aims to isolate actinobacteria from mangrove swamps and to characterize their QQ enzymes as a potential remediation. A total of nine soil actinobacteria were isolated from mangrove swamps soil samples using selective agar. QQ activity was detected by screening of AHL degradation using C. violaceum CV026 biosensor assay and rapid resolution liquid chromatography (RRLC) analysis. All nine actinobacteria were able to degrade different QS molecules namely N-hexanoyl-L-homoserine lactone (C6-HSL), N-(3-oxo-hexanoyl)-L-homoserine lactone (3-oxo-C6-HSL) and N-(3-hydroxyhexanoyl)-L-homoserine lactone (3-hydroxy-C6-HSL). It is found that these actinobacteria degrade AHL via enzymatic reaction through lactonase activity. For future work, next generation sequencing should be done to identify the QQ gene(s) involved.